Outcomes for upper gastrointestinal bleeding during the first wave of the COVID‐19 pandemic in the Toronto area. Issue 5 (28th February 2022) - Khan, Rishad; Saha, Sudipta; Gimpaya, Nikko; Bansal, Rishi; Scaffidi, Michael A; Razak, Fahad; Verma, Amol A; Grover, Samir C
Abstract: Background and Aim: Changes to endoscopy service availability during the COVID‐19 pandemic may have affected management of upper gastrointestinal bleeding (UGIB). The aim of this study was to describe the impact of the pandemic on UGIB outcomes in the Toronto area in Canada. Methods: We described all adults admitted to general medicine wards or intensive care units at six hospitals in Toronto and Mississauga, Canada, with UGIB during the first wave of the COVID‐19 pandemic (March 1 to June 30, 2020) and compared them with a historical cohort (March 1 to June 30, 2018 and 2019). We compared clinical outcomes (in‐hospital mortality, length of stay, 30‐day readmission, intensive care utilization, receipt of endoscopy, persistent bleeding, receipt of second endoscopy, and need for angiographic or surgical intervention) using multivariable regression models, controlling for demographics, comorbidities, and severity of clinical presentation. Results: There were 82.5 and 215.5 admissions per month for UGIB during the COVID‐19 and control periods, respectively. There were no baseline differences between groups for demographic characteristics, comorbidities, or severity of bleeding. Patients in the COVID‐19 group did not have significantly different unadjusted (3.9% vs 4.2%, P = 0.983) or adjusted mortality (adjusted odds ratio [OR] = 0.64, 95% confidence interval [CI] = 0.25–1.48, P = 0.322). Patients in COVID‐19 group were less likely to receive endoscopy for UGIB in the unadjusted (61.8% vs 71.0%, P = 0.003) and adjusted (adjusted OR = 0.64, 95% CI = 0.49–0.84, P < 0.01) models. There were no differences between groups for other secondary outcomes. Conclusions: While patients admitted for UGIB during the first wave of the pandemic were less likely to receive endoscopy, this had no impact on mortality or any secondary outcomes.